2023
DOI: 10.1172/jci.insight.157091
|View full text |Cite
|
Sign up to set email alerts
|

IL-13RA2 downregulation in fibroblasts promotes keloid fibrosis via JAK/STAT6 activation

Abstract: Keloid is considered as a fibro-proliferative disease characterized by chronic inflammation that is induced following skin injury. Deciphering the underlying mechanism of keloid formation is essential for improving treatment outcomes. Here, we found that more macrophages were activated towards M2 subtype in keloid dermis when compared to normal dermis. Western Blot revealed that the level of phosphorylated STAT6, a known inducer of M2 polarization, was higher in keloid fibroblasts as opposed to fibroblasts fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…With its identification as one of the downstream targets of EGFR and mutant EGFRvIII [36,37], IL-13Rα2 was considered to more easily promote the proliferation, migration and invasion of tumour cells rather than EGFR activation through the Src/PI3K/ Akt/mTOR signalling pathway, whereas EGFR activation mainly promotes cancer cell proliferation [38,39]. JAK-STAT6 signalling pathway was also negative regulated by upstream IL-13Rα2 [25], interestingly, the STAT6 in A172 cells has been found significantly activated due to the inhibition of IL-13Rα2 by targeted siRNA or VNAR (Figure S6), which may contribute to the subsequent inhibitory effect (or apoptosis) of glioma cells. This finding makes IL-13Rα2 a useful target for novel therapies that could be designed to selectively inhibit malignant progression of glioma [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With its identification as one of the downstream targets of EGFR and mutant EGFRvIII [36,37], IL-13Rα2 was considered to more easily promote the proliferation, migration and invasion of tumour cells rather than EGFR activation through the Src/PI3K/ Akt/mTOR signalling pathway, whereas EGFR activation mainly promotes cancer cell proliferation [38,39]. JAK-STAT6 signalling pathway was also negative regulated by upstream IL-13Rα2 [25], interestingly, the STAT6 in A172 cells has been found significantly activated due to the inhibition of IL-13Rα2 by targeted siRNA or VNAR (Figure S6), which may contribute to the subsequent inhibitory effect (or apoptosis) of glioma cells. This finding makes IL-13Rα2 a useful target for novel therapies that could be designed to selectively inhibit malignant progression of glioma [40].…”
Section: Discussionmentioning
confidence: 99%
“…With further studies on IL‐13Rα2, it has been found that IL‐13Rα2 is closely connected with glioma, especially malignant glioma. Rahaman et al [24] demonstrated that the intracellular domain of IL‐13Rα2 can bind type 2 IL‐4Rα and the inhibition was mediated through the interaction between the short intracellular domain of the IL‐13Rα2 protein and the cytoplasmic domain of the IL‐4Rα chain that harbours the STAT6 docking sites, thereby inhibiting the subsequent activation of the Janus tyrosine kinase‐signal transducer and activator of transcription (JAK‐STAT) pathway [25]. This may contribute the development of gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we observed positive correlations between CTHRC1 and THBS2 gene expression levels with the presence of IL‐13, TGFB1 and TGFB3. Remarkably, IL‐13 emerged as a pivotal driver of progressive fibrosis and has been found to be elevated in patients with keloid scars 45–48 . Existing reports indicate that IL‐13 induces the production of anti‐apoptotic proteins and directly enhances myofibroblast function, further implicating its role in fibrotic processes 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, IL‐13 emerged as a pivotal driver of progressive fibrosis and has been found to be elevated in patients with keloid scars. 45 , 46 , 47 , 48 Existing reports indicate that IL‐13 induces the production of anti‐apoptotic proteins and directly enhances myofibroblast function, further implicating its role in fibrotic processes. 48 Additionally, the TGF‐β superfamily, well‐established as an important mediator of tissue repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation